Is GDP growth always a measure of success? (W poszukiwaniu zielonego ładu, 2022)
The chapter provides a critical analysis of the use of the natural environment and its protection in calculating GDP. Both the exploitation of natural resources and the broadly understood environmental protection industry contribute to GDP growth, regardless of their resource-intensive nature. In resource-rich developing countries, it is also a challenge to properly estimate the resource rent and manage its use for the benefit of local communities. The attempts to green the economic growth and national accounts to date, although they have brought some intellectual unrest, have not released us from the problems resulting from treating economic activity related to the exploitation and degradation of the environment as GDP-generating. The need to support the production processes with energy generates another problem for mankind, the excess of energy is being reflected towards the Earth, which contributes to climate change. Since any activity which increases GDP leaves a carbon footprint, we are in a trap. By remaining slaves to economic growth, we can make Earth completely uninhabitable to life as we know it.